Neuropsychological decrements in midlife type-2 diabetes are not associated with peripheral NLRP3 inflammasome responsiveness - Dyer, Adam H.; Batten, Isabella; Reddy, Conor; Townsend, Liam; Woods, Conor P.; O’Neill, Desmond; Gibney, James; Kennelly, Sean P.; Bourke, Nollaig M. (Frontiers in Immunology, 2022)
Midlife Type 2 Diabetes Mellitus (T2DM) is associated with an increased risk of Alzheimer Disease (AD) in later life, with altered inflammatory responses postulated as key pathological drivers. Previous studies have demonstrated increased responsiveness to NLR family pyrin domain containing 3 (NLRP3) inflammasome agonists, both in individuals with untreated T2DM in addition to those with established AD. We hypothesised that peripheral NLRP3 inflammasome responses may be altered during the early stages of T2DM-related cognitive dysfunction. Here, we assessed the relationship between NLPR3 responses in peripheral blood mononuclear cells (including to Aβ-42, the putative pathogenic protein in AD) and neuropsychological performance in uncomplicated midlife T2DM to identify early signatures of immune dysregulation which may predispose to later cognitive decline. We recruited a cross-sectional cohort of middle-aged adults with uncomplicated T2DM and matched Healthy Controls (HCs) for comprehensive neuropsychological assessment and in vitro PBMC responses to a range of NLRP3 agonists were assessed. T2DM was associated with subtle decrements on neuropsychological tests of delayed memory and executive function (both p<0.05). Overall, there were no differences between T2DM and HCs in immune responses induced by NLRP3 agonists. Further, we observed no relationship between the subtle neuropsychological decrements observed in T2DM and PBMC responsiveness to NLRP3 agonists. Our data suggests that peripheral NLRP3 inflammasome response dysregulation may not play a role in the early stages of cognitive dysfunction in midlife T2DM. Further longitudinal studies are warranted to examine the contribution of peripheral NLRP3 responses towards disease pathology and as cognitive decline accelerates in T2DM.